Electronic governance for context-specific public service delivery: a survey of the literature - Tavares, António (2016)
Based on the latest trends of government digitization efforts, this paper presents a survey of the literature illustrating how governments are using Information and Communication Technologies (ICT) to deliver public services pursuing concrete development goals and taking into account specific needs of the local context. Based on the survey, we illustrate examples of context-specific public service delivery and propose a research framework to guide future research on the area. The relevance of this work relies on the latest commitment of governments to pursue the 2030 development agenda, since the framework provides a roadmap to further investigate how to locally design public services to achieve sustainable development goals leveraging on ICT.